Ultrastructural Study on Tissue Alterations Caused by Trypanosomatids in Experimental Murine Infections - Finol, Héctor J.; Roschman-González, Antonio (Frontiers in Public Health, 2014)
The ultrastructural study in different tissues of mice experimentally infected with isolates of Trypanosoma evansi, Trypanosoma cruzi, and Leishmania mexicana reveals changes in cardiac myocytes, skeletal muscle fibers, and hepatic, adrenal, kidney, and spleen cells. Some of these changes were cytoarchitectural and others consisted of necrosis. Alterations in the microvasculature were also found. The mononuclear cell infiltrate included neutrophils, eosinophils, and macrophages. This work shows that diverse mice tissues are important target for trypanosomatids.